2013
DOI: 10.1111/corg.12015
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Accounting Conservatism: Evidence from the Banking Industry

Abstract: Manuscript Type Empirical Research Question/Issue In this paper, we empirically investigate whether US listed commercial banks with effective corporate governance structures engage in higher levels of conservative financial accounting and reporting. Research Findings/Insights Using both market‐ and accrual‐based measures of conservatism and both composite and disaggregated governance indices, we document convincing evidence that well‐governed banks engage in significantly higher levels of conditional conservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
2
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 115 publications
(226 reference statements)
3
74
2
13
Order By: Relevance
“…In particular, the "specialness" of banks, as analytically discussed by John et al (2016), Zalewska (2016), and Srivastav and Hagendorff (2016) in this special issue, requires an analytical framework that does not focus exclusively on protecting the interests of equity claimants but also expands to incorporating non-shareholder constituencies' interests such as depositors and the society-at-large. In the presence of potentially conflicting interests among heterogeneous constituents, the effectiveness of traditional governance mechanisms is also limited for the case of banks (see Grove, Patelli, Victoravich, & Xu, 2011;Leventis, Dimitropoulos, & Owusu-Ansah, 2013). More research is therefore warranted on the corporate governance of banks and, more specifically, on determining what constitutes good governance for financial entities.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
“…In particular, the "specialness" of banks, as analytically discussed by John et al (2016), Zalewska (2016), and Srivastav and Hagendorff (2016) in this special issue, requires an analytical framework that does not focus exclusively on protecting the interests of equity claimants but also expands to incorporating non-shareholder constituencies' interests such as depositors and the society-at-large. In the presence of potentially conflicting interests among heterogeneous constituents, the effectiveness of traditional governance mechanisms is also limited for the case of banks (see Grove, Patelli, Victoravich, & Xu, 2011;Leventis, Dimitropoulos, & Owusu-Ansah, 2013). More research is therefore warranted on the corporate governance of banks and, more specifically, on determining what constitutes good governance for financial entities.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
“…Leventis et al . (2013) showed that managers and policy‐makers of a business must focus on corporate governance in order to improve information quality. For instance, Firth et al .…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…For example, financial reporting quality, measured as fewer restatements and discretionary accruals, was improved by the audit committee having greater legal and accounting expertise (Krishnan et al, 2011), as well as a greater number of accounting and industry experts (Cohen et al, 2013). Similarly, fully independent and active audit committees were associated with a reduced likelihood of restatements and larger recognition of loan loss provisions (Abbott et al, 2004;Leventis et al, 2013). Indeed, in pre-IPO firms the mere presence of an audit committee can reduce accruals (Venkataraman et al, 2008).…”
Section: Outcomes Of Board Committeesmentioning
confidence: 99%